The role of the orthopaedic surgeon in the prevention of refracture in patients treated surgically for fragility hip and vertebral fracture - Beraldi, Rosella (CIC Edizioni Internazionali, 2014)
The role of the orthopaedic surgeon in the treatment of patients with fragility fractures is twofold: the conservative or surgical treatment of the fracture, and the prevention of further fractures, establishing diagnostic and therapeutic procedures for osteoporosis. We evaluated 72 patients treated surgically for fragility vertebral fracture and 801 patients treated surgically for fragility hip fracture, operated from 2009 to 2010 at O.U. Orthopaedics and Traumatology of S.M. Annunziata Hospital of Florence, that have followed a treatment for refractures prevention according to the TARGET (Appropriate Treatment for Refractures GEriatric in Tuscany) Project of Tuscany Region. The average follow-up was 34 months. Patients with vertebral fracture treated for refractures prevention were 58 (80.6%), while patients with hip fracture treated for refractures prevention were 307 (38.3). RESULTS: the number of patients with vertebral fracture who had a refracture in the first two years after surgery was 12 (16.6%), of which 9 patients were not treated for osteoporosis. The percentage of refracture at 1 year after surgery in patients with hip fractures was 3.19% in 2009 and 2.17% in 2010, compared to 5.16% of refracture of 2006 when the TARGET Project was not yet started. Mortality at 1 year after surgery in patients with hip fracture treated for osteoporosis was 19% compared to 25–31% in the patients not treated for osteoporosis.